(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This study intends to highlight the possible significant relationship that may exists between Information Technology (IT) in the perceived usefulness of Activity-Based Costing (ABC) information as compared to the traditional costing across three different campus clusters of higher education institutions (HEI) in Malaysia. The perceived usefulness of ABC was represented by two elements, namely i) quality, and ii) functionality of costing system. The respondents were selected using disproportionate stratified random sampling method among the users of costing information in the biggest public university in Malaysia with a multi-campus university system. Among the twelve branch campuses across the country, the data was collected using structured postal questionnaires that were distributed to 96 respondents. The result indicated that there is no significant difference of perceived usefulness of information produced by ABC system across all three type campus clusters under study. Furthermore, statistical analysis also shown that there is no statistically significant interaction across three types of campus clusters to affect Perception of Usefulness (POU). As the findings from this study found to be contradict from the previous studies , these might be due to the nature of a multi-campus university system which practising the centralised administration across all branch campuses. In addition to that, unlike previous studies, this study extended the applicability of IT in two dimensions of university administrations, i.e., as a support system for administration and as a management tool.